Evaluation of brans of different rice varieties for their antioxidative and antihyperglycemic potentials - Abu Bakar, Tanko; Marikkar, Nazrim; Salleh, Abubakar; Azlan, Azrina; Jivan, Make (Blackwell Publishing Ltd., 2017)
The aim of this study was to compare the antioxidant and antihyperglycaemic potentials of bran extracts of seven traditional rice varieties against those of three commercial varieties. The total polyphenolic content and antioxidant activities, the α-amylase and α-glucosidase inhibitory potentials of the rice bran extracts were studied in vitro using relevant assays. The results showed that the rice bran extracts of traditional varieties namely, Beras merah and Beras hitam displayed significantly higher α-glucosidase inhibition (96.56 and 81.52%) and α-amylase inhibition (88.44 and 84.27%) than the other varieties. Being high in polyphenolic content, they tended to display better anti-oxidant capacities than the commercial varieties. Hence, brans of traditional rice varieties such Beras merah and Beras hitam could be potentially useful as raw materials for nutritional supplements and natural anti-diabetic agents. Practical Application: The findings of this study highlighted the anti-oxidative, α-amylase and α-glucosidase inhibitory potentials of some rice brans obtained from Malaysian rice varieties. Since the traditional rice varieties (Beras Merah and Beras Hitam) exhibit significantly higher α-amylase and α-glucosidase inhibition, they could be harnessed as raw materials for preparation of ingredients for pharmaceuticals, and nutraceuticals intended for diabetes management. The findings might give impetus to the Malaysian paddy industry to expand cultivation of Beras Merah and Beras Hitam to produce more bran for value added product formulations for people with special dietary requirements.